Experimental and numerical study on lateral behaviour of geosynthetic-reinforced pile foundation system. Issue 6 (1st December 2014) - Taha, A.; El Naggar, M.H.; Turan, A.
Abstract : ABSTRACT: This paper introduces an innovative use of polymer strips as part of a novel foundation concept, polymer strips reinforced pile foundation system, where polymer strips are used to enhance the lateral resistance of a pile foundation. The lateral static behaviour of this foundation system was evaluated using a series of reduced scale physical model tests performed on the model foundation installed in different soil beds contained in a small size soil container. These soil beds included: a soil bed representing the base case (soft clay overlying sand layer); a soil model representing the conventional ground replacement solution (the glyben layer sandwiched between an aggregate layer from top and a sand layer from bottom) and a soil model representing the proposed novel geosynthetic-reinforced backfill (the glyben layer sandwiched between a geosynthetic-reinforced aggregate layer from top and a sand layer from bottom). A one directional loading system was attached to the soil container containing a three-layer model soil deposit, which included a layer of synthetic clay (modified glyben) sandwiched between a lower and a surficial granular layer, was used. The model pile-cap system was installed through the surficial granular layer, which was reinforced using a microgrid mesh and underlying clay and sand layers. A series of lateral static pull tests have been conducted to investigate the influence of the polymer strip reinforcement on the foundation system behaviour. This study also presents the results of a three-dimensional finite-element analyses which was based on models calibrated against physical test results. The experimental results and numerical analyses showed that the lateral resistance of a pile cap system was enhanced by the microgrid mesh embedded in the surficial granular layer. The results also showed that the lateral resistance of the pile cap system was significantly influenced by the thickness of engineered backfill.